Micro-regional planning: evidence-based community buy-in for health development in five of Mexico's poorest rural districts - Arrizón Ascencio; Andersson Neil; Ledogar Robert J (BMC, 2011)
Abstract Background Community participation was a core tenet of Primary Health Care as articulated in the 1970s. How this could be generated and maintained was less clear. This historical article describes development of protocols for evidence-based community mobilisation in five local administrative units (municipios) in the Mexican state of Guerrero between 1992 and 1995. Methods A sample of five to eight sentinel sites represented each of the most impoverished municipalities of the poorest five of the state's seven regions. A 1992 baseline survey of diarrhoea and its actionable determinants provided the substrate for discussion with local planners and communities. Municipal planners used different strategies to promote participation. In one municipality, new health committees took control of water quality. In another, municipal authorities hired health promoters; a song promoted oral rehydration, and house-to-house interpersonal discussions promoted chlorination. In the poorest and most mountainous municipality, radio casera (home-made radio) soap operas used local "stars". In the largest and most disparate municipality, a child-to-family scheme relied on primary and secondary school teachers. The research team assessed outcomes at intervals and used the results to reinforce local planning and action. Results Diarrhoea rates declined in all five municipalities, and there were several positive intermediate outcomes from the communication strategies - changing knowledge, household practices and uptake of services. There was a strong link between specific contents of the communication package and the changing knowledge or practices. Conclusions Apart from these evidence-based interventions, other factors probably contributed to the decline of childhood diarrhoea. But, by monitoring implementation of planning decisions and the impact this has at community level, micro-regional planning can stimulate and reinforce actions likely to improve the health of communities. The process empowered municipalities to get access to more resources from the state government and international agencies.